Early retirement among Danish female cleaners and shop assistants according to work environment characteristics and upper extremity complaints: an 11-year follow-up study - Jensen, Lone Donbæk (BMC Musculoskelet Disord, 2016)
BACKGROUND: Studies have shown a negative social gradient in the incidence of early retirement. To prevent undesired early retirement, there is a need for knowledge of specific predictors in addition to social factors with a limited potential for change. The main purpose of this study was to examine musculoskeletal complaints and working conditions as predictors of early retirement among Danish female cleaners. METHODS: Using Cox regression with an adjustment for extraneous factors, we compared the risk of disability pension and retirement before the nominal retirement age (65 years) in an 11-year cohort study with registry-based follow-up of 1430 female cleaners and 579 shop assistants. In subsequent analyses of female cleaners, disability pension and voluntary early retirement were modeled according to work characteristics and upper extremity complaints. RESULTS: The adjusted hazard rate (HR) for disability pension among cleaners compared to the control group was 2.27 (95 % CI 1.58 to 3.28) and, for voluntary early retirement, 1.01 (95 % CI 0.85 to 1.20). In the subset of cleaners, the predictors of disability pension were persistent shoulder pain HR: 1.98 (95 % CI 1.47 to 2.67), elbow pain HR: 1.41 (95 % CI 1.02 to 1.94) and symptoms of nerve entrapment of the hand HR: 1.58 (95 % CI 1.14 to 2.20). Predictors of voluntary early retirement were persistent shoulder pain HR: 1.40 (95 % CI 1.16 to 1.67) and floor mopping for more than 10 h per week HR: 1.20 (95 % CI 1.03 to 1.40). CONCLUSION: Cleaners have a twofold higher risk of disability pension compared to the control group. Risk factors for disability pension among cleaners were persistent shoulder and elbow pain together with symptoms of nerve entrapment of the hand. The findings of specific health related predictors of early retirement could be used in secondary prevention with targeted temporary reduced workload.